2015
DOI: 10.1007/s11595-015-1191-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boron content on the microstructure and magnetic properties of non-oriented electrical steels

Abstract: The effects of boron content in the range of 0-0.0082 wt%, on the inclusion type, microstructure, texture and magnetic properties of non-oriented electrical steels have been studied. After fi nal annealing, the addition of excess boron(w(Bt)>0.004 1 wt%) led to the formation of Fe 2 B particles. As boron content increased, grain size increased and reached a maximum in steel with 0.004 1 wt% boron. Furthermore, steel containing 0.004 1 wt% boron had the strongest {100} fi ber texture, Goss texture and the weake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The best magnetic properties were achieved with 0.004 wt.% B content, with core loss 3.616 W/kg and magnetic induction 1.792 T [70]. [78], as illustrated in Figure 9. As shown in Figure 9a, with the increase of B content up to 0.004 wt.%, the grain size increased.…”
Section: Influence Of B Contentmentioning
confidence: 97%
See 1 more Smart Citation
“…The best magnetic properties were achieved with 0.004 wt.% B content, with core loss 3.616 W/kg and magnetic induction 1.792 T [70]. [78], as illustrated in Figure 9. As shown in Figure 9a, with the increase of B content up to 0.004 wt.%, the grain size increased.…”
Section: Influence Of B Contentmentioning
confidence: 97%
“…In the range of 0.0075-0.053 wt.% B content for Fe-6.5 wt.% electrical steels, Kim observed that an increase of B content might also have a grain-refining effect, and also improve bending strength and ductility at room temperature [77]. The influence of B in Fe-1.35 wt.% electrical steels has also been studied [78], as illustrated in Figure 9. As shown in Figure 9a, with the increase of B content up to 0.004 wt.%, the grain size increased.…”
Section: Influence Of B Contentmentioning
confidence: 99%
“…A review of the scientific literature shows that much work on the use of boron in metallurgy is devoted to its effect on the structure and properties of the processed metal (steel, etc.) [1][2][3][4][5][6][7][8][9][10][11][12][13]. The authors of work [2] noted a positive effect of alloying the metal with aluminum on the hardenability and mechanical properties of thick steel boron micro-alloy.…”
Section: Actuality Scientific Significancementioning
confidence: 99%
“…Complex studies have been carried out to study the effect of boron on the structure, the tendency to carburization and the resistance to inter-crystalline corrosion (ICC) of low-carbon austenitic chromium-nickel steel as a function of the thermal treatment temperature [4]. It has been established that the presence of 0.003% B has a positive, and 0.03 and 0.06% B and to a lesser extent 0.2 ... 0.4% B -a negative effect on the resistance against ICC of steel 02X17H15 in weakly oxidative media after quenching at temperatures above 1100 0 C. The authors of [5] investigated the effect of boron additives in the metal to 0.0082% and determined that if [B] > 0.004%, then after the final annealing, the Fe 2 B phase is formed. This steel receives a favorable structure and improved magnetic properties.…”
Section: Introductionmentioning
confidence: 99%